Analysis of the phenotypic variants of polycystic ovarian syndrome in women of reproductive age group - Basnet, Pritha; Chhetry, Manisha; Shah, Deepa; Basnet, Tulasa; Sitaula, Sarita; Dahal, Mona (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To identify the different phenotypic variant of PCOS in women of reproductive age group and to assess the hormonal and metabolic profile of women with PCOS. Methods: This Prospective descriptive study was conducted in the Department of Obstetrics and Gynecology, BPKIHS, Dharan for a period of one year from July 2020 to June 2021. All Women presenting to Gynecology OPD with complaints of menstrual irregularity and clinical features of hyperandrogenism were assessed and evaluated for polycystic ovarian syndrome. BMI was calculated. Hormonal Profile (serum LH, FSH and testosterone) and metabolic parameters (fasting blood sugar and lipid profile) were studied; and then further categorized into different phenotypic variants. All data were stored in Microsoft excel format and analyzed using SPSS version 11.5. using descriptive statistics. Results: Total of 80 cases of PCOS were enrolled during the study period. The most common phenotypic variant was Type B (60%) followed by Type D (30%). The mean BMI was 22.4± 4.2kg/m2 . All PCOS cases presented with menstrual irregularity as the primary complaint. Conclusions: Anovulatory PCOS was the most common phenotypic variant in our study population. This study did not find obese PCOS hence emphasizing the need of evaluation in lean women with or without hyperandrogenism presenting with menstrual irregularities.